2020
DOI: 10.1017/s0007114520001403
|View full text |Cite
|
Sign up to set email alerts
|

Effect of garlic powder supplementation on hepatic steatosis, liver enzymes and lipid profile in patients with non-alcoholic fatty liver disease: a double-blind randomised controlled clinical trial

Abstract: Non-alcoholic fatty liver disease (NAFLD) includes a range of disorders from simple steatosis to non-alcoholic steatohepatitis. There is no proven drug treatment for NAFLD, and diet modification is considered part of the main line of treatment for this disease. The aim of this study was to investigate the efficacy of garlic supplementation in NAFLD patients. The effect of garlic powder supplementation on hepatic steatosis, liver enzymes and lipid profile was investigated in NAFLD patients. Ninety NAFLD patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 28 publications
2
35
0
Order By: Relevance
“…Garlic increases the phosphorylation of AMP‐activated protein kinase (AMPK), down‐regulates the levels of sterol regulatory element binding protein‐1 (SREBP‐1) as well as acetyl‐CoA carboxylase and fatty acid synthase, regulates lipogenesis, modulates the activity of nuclear factor kappa‐B (NF‐κB) pathways, improves gut microbiota dysbiosis, and consequently can improve hepatic steatosis (Chen et al, 2019; Hwang et al, 2013; Maeda et al, 2019; Ried et al, 2018). Consistent with our findings, garlic powder supplementation for 3 months improved hepatic steatosis and serum levels of alanine transaminase (ALT), aspartate transaminase (AST) as well as GGT in patients with NAFLD (Sangouni, Mohammad Hosseini Azar, & Alizadeh, 2020a). In addition, the study of Kim, Kang, Roh, Choi, and Song (2017) demonstrated a significant improvement in the levels of liver enzymes in subjects with elevated serum GGT, after garlic supplementation for 12 weeks.…”
Section: Discussionsupporting
confidence: 86%
“…Garlic increases the phosphorylation of AMP‐activated protein kinase (AMPK), down‐regulates the levels of sterol regulatory element binding protein‐1 (SREBP‐1) as well as acetyl‐CoA carboxylase and fatty acid synthase, regulates lipogenesis, modulates the activity of nuclear factor kappa‐B (NF‐κB) pathways, improves gut microbiota dysbiosis, and consequently can improve hepatic steatosis (Chen et al, 2019; Hwang et al, 2013; Maeda et al, 2019; Ried et al, 2018). Consistent with our findings, garlic powder supplementation for 3 months improved hepatic steatosis and serum levels of alanine transaminase (ALT), aspartate transaminase (AST) as well as GGT in patients with NAFLD (Sangouni, Mohammad Hosseini Azar, & Alizadeh, 2020a). In addition, the study of Kim, Kang, Roh, Choi, and Song (2017) demonstrated a significant improvement in the levels of liver enzymes in subjects with elevated serum GGT, after garlic supplementation for 12 weeks.…”
Section: Discussionsupporting
confidence: 86%
“…84,85 In addition, (1 R ,3 S )-1-methyl-1,2,3,4-tetrahydro-β-carboline-3-carboxylic acid obtained from garlic was found to prevent adiposity by regulating the expression of genes involved in the lipid metabolism of adipocytes, downregulating lipogenic genes and upregulating lipolytic genes. 86 Likewise, experimental studies are in agreement with these findings, observing garlic supplementation to be beneficial in reducing plasma levels of total cholesterol and LDL in patients with nonalcoholic fatty liver disease, 87 polycystic ovary syndrome, 88 and hyperlipidemia. 89–91 In contrast, Jung et al observed that daily supplementation of 6 g of black AGE in patients with hypercholesterolemia did not decrease LDL, although they did report an increase in HDL.…”
Section: Therapeutic Activity Against Diseasessupporting
confidence: 56%
“…Food & Function be beneficial in reducing plasma levels of total cholesterol and LDL in patients with nonalcoholic fatty liver disease, 87 polycystic ovary syndrome, 88 and hyperlipidemia. [89][90][91] In contrast, Jung et al observed that daily supplementation of 6 g of black AGE in patients with hypercholesterolemia did not decrease LDL, although they did report an increase in HDL.…”
Section: Reviewmentioning
confidence: 99%
“…At the end of the study, features of hepatic steatosis were significantly reduced in the treatment group, compared with the control group. Specifically, ALT, AST, and gamma-GT, but not ALP levels, significantly decreased, similar to TC, TG, and LDL-C, which also decreased in the treatment group, compared with the control group [41]. The same NAFLD population, in a parallel study, revealed a reduction in HOMA-IR, as well as a significant increase in skeletal muscle mass, serum concentration of superoxide dismutase, and total antioxidant capacity in the treatment group [42].…”
Section: Garlicmentioning
confidence: 75%